Strontium adsorbent and its manufacturing method
A tailored layered manganese oxide adsorbent with controlled composition and properties addresses swelling issues, achieving high strontium adsorption and retention in aqueous environments.
Patent Information
- Application Number
- JP2021025942
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-22
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-02-22
AI Technical Summary
Existing layered manganese oxides used for strontium removal suffer from swelling and disintegration in aqueous solutions, leading to poor shape retention and insufficient strontium adsorption capacity.
A strontium adsorbent composed of layered manganese oxide with a specific composition formula Na x K y MnO 2 (0.05≦x, 0.05≦y, 0.31≦x+y≦0.60) and controlled crystallite diameter, interlayer distance, BET specific surface area, and particle size, ensuring both strontium adsorption performance and shape retention.
The adsorbent exhibits excellent strontium adsorption performance and shape retention, maintaining structural integrity in wet conditions while effectively removing strontium from processing liquids.
Abstract
Description
[Technical field]
[0001] The present invention relates to a strontium adsorbent and a method for producing the same, and more particularly to a strontium adsorbent containing layered manganese oxide and a method for producing the same. The strontium adsorbent of the present invention is useful for efficiently removing strontium from a treatment solution. [Background technology]
[0002] Layered manganese oxides are known as adsorbents capable of removing harmful ions from aqueous solutions.
[0003] Patent Document 1 discloses a layered manganese oxide, which is synthesized by baking manganese and sodium raw materials at 400° C. or higher and has sodium ions present between the layers, as an adsorbent for strontium ions in seawater.
[0004] On the other hand, Patent Document 2 discloses a layered manganese oxide in which potassium ions exist between layers, which is synthesized by firing a manganese raw material and a potassium raw material at 400° C. or higher. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6679000 [Patent Document 2] JP 2020-15042 A Summary of the Invention [Problem to be solved by the invention]
[0006] The layered manganese oxide in Patent Document 1 is a sodium-type layered manganese oxide with an interlayer distance of approximately 5.5 Å, known as dehydrated birnessite. However, the interlayer distance of dehydrated birnessite increases significantly upon hydration in an aqueous solution, which poses the problem that the adsorbent is prone to swelling and collapse.
[0007] The layered manganese oxide in Patent Document 2 is a potassium type layered manganese oxide with an interlayer distance of 7.0 to 7.2 Å, which is close to that of hydrated birnessite, and is therefore unlikely to collapse due to swelling. However, its strontium adsorption capacity is insufficient. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. That is, the present invention is a layered manganese oxide that contains at least sodium, potassium, and manganese and has the composition formula Na x K y MnO2 (wherein the formula satisfies 0.05≦x, 0.05≦y, and 0.31≦x+y≦0.60), the crystallite diameter is 20 Å or more and 250 Å or less, and the BET specific surface area is 1 m 2 / g or more 10m 2 / g or less, and contains layered manganese oxide with an interlayer distance of 7.0 Å to 7.6 Å, and has an average particle diameter D 50 The strontium adsorbent is characterized in that it is a powder having a size of 50 μm or more and less than 200 μm. Effect of the Invention
[0009] The present invention has an effect of providing an adsorbent that has excellent shape retention because the interlayer distance is unlikely to increase, and also has excellent strontium adsorption performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below.
[0011] The strontium adsorbent of the present invention is composed of a layered manganese oxide containing at least sodium, potassium and manganese, and has the composition formula Na x K y MnO2 (wherein the formula satisfies 0.05≦x, 0.05≦y, and 0.31≦x+y≦0.60), the crystallite diameter is 20 Å or more and 250 Å or less, and the BET specific surface area is 1 m 2 / g or more 10m2 / g or less, and contains layered manganese oxide with an interlayer distance of 7.0 Å to 7.6 Å, and has an average particle diameter D 50 The strontium adsorbent is characterized in that it is a powder having a size of 50 μm or more and less than 200 μm.
[0012] The layered manganese oxide contained in the strontium adsorbent of the present invention is composed of layered manganese oxide containing at least sodium, potassium, and manganese, and has the composition formula Na x K y MnO2 (wherein the formula satisfies 0.05≦x, 0.05≦y, and 0.31≦x+y≦0.60). Strontium is adsorbed to the layered manganese oxide by ion exchange between the strontium ions in the treatment liquid and the cations between the layers. Therefore, the greater the content of sodium and potassium, the more adsorption sites there are, leading to improved strontium adsorption performance. Therefore, in the present invention, the range is 0.31≦x+y≦0.60, but preferably the range is 0.32≦x+y≦0.60, making it possible to achieve both a layered structure and adsorption performance. The inclusion of both sodium and potassium as interlayer cations leads to the compatibility of strontium adsorption performance and shape retention. The inclusion of sodium improves strontium adsorption performance, but since the interlayer distance of layered manganese oxide in which only sodium is an interlayer cation varies greatly between dry and wet conditions, there is a concern that the adsorbent powder will disintegrate finely in the liquid, making it difficult to recover the material after strontium adsorption. Layered manganese oxide containing potassium has a nearly constant interlayer distance when dry and when wet, and improves shape retention. By containing both sodium and potassium, the layered manganese oxide can achieve both strontium adsorption performance and shape retention. The sodium and potassium contents are preferably 0.05≦x and 0.05≦y, and more preferably 0.1≦x and 0.1≦y.
[0013] The layered manganese oxide contained in the strontium adsorbent of the present invention has a crystallite diameter of 20 Å or more and 250 Å or less. From the viewpoint of mass transfer within the particle, the smaller the crystallite diameter, the greater the strontium adsorption performance. However, if the crystallite diameter is too small, it becomes close to amorphous and it is considered difficult to retain strontium inside the crystal. Therefore, by making the crystallite diameter 20 Å or more and 250 Å or less, good strontium adsorption performance can be obtained. The crystallite diameter is preferably 20 Å or more and 200 Å or less, more preferably 30 Å or more and 100 Å or less. The crystallite diameter mentioned here is the crystallite diameter obtained by powder X-ray diffraction using CuKα as a radiation source, using the Scherrer formula (constant K=0.9) from the peak of the 001 plane.
[0014] The layered manganese oxide contained in the strontium adsorbent of the present invention has a BET specific surface area of 1 m 2 / g or more 10m 2 The contact area between the layered manganese oxide and the treatment liquid has a large effect on the strontium adsorption performance and the strength of the layered manganese oxide. 2 If it is less than 10m / g, the adsorption performance is low. 2 When the specific surface area exceeds 1 m, it is highly likely that manganese tetraoxide is formed as a by-product phase. Manganese tetraoxide does not have the ability to adsorb strontium, so its formation reduces the strontium adsorption ability of the powder. The BET specific surface area is 1 m 2 / g or more 5m 2 / g or less is preferable.
[0015] The strontium adsorbent of the present invention has an average particle diameter D 50 The average particle size D is 50 μm or more and less than 200 μm. 50 If the average particle diameter D is less than 50 μm, it is considered that the filterability when separating the adsorbent from the liquid will be poor. 50 If the average particle diameter D is more than 200 μm, it takes a long time for the liquid to penetrate into the adsorbent particles, making it unsuitable for use as an adsorbent powder. 50 In this specification, the average particle diameter D50 " means the particle size at 50% cumulative volume in the particle size distribution determined by a laser diffraction / scattering method using a spherical approximation.
[0016] Strontium is adsorbed to the layered manganese oxide by ion exchange between the strontium ions in the treatment solution and the cations between the layers. This is said to be because there is an interlayer distance suitable for the ionic radius or hydration radius of the exchanged strontium. From the viewpoint of strontium adsorption performance, the interlayer distance of the potassium type layered manganese oxide contained in the strontium adsorbent of the present invention is 7.0 Å or more and 7.6 Å or less. The interlayer distance mentioned here is represented by the distance between the basal planes of the opposing manganese layers, and can be determined from the peak representing the 001 plane of the XRD diffraction peak. The layered manganese oxide with an interlayer distance of 7.0 Å or more and 7.6 Å or less has diffraction peaks at 2θ=12.2±0.6°, 2θ=24.6±1.5°, and 2θ=36.5±2.0° in powder X-ray diffraction using CuKα as a radiation source. If the interlayer distance is less than 7.0 Å, when the layered manganese oxide is introduced into an aqueous solution, the interlayer distance will vary greatly when water is inserted between the layers or when strontium is adsorbed, raising concerns about the collapse of the adsorbent particles, and if the interlayer distance is more than 7.6 Å, there is a concern about a decrease in strontium adsorption performance. It is preferable that the interlayer distance is 7.1 Å or more and 7.5 Å or less.
[0017] The layered manganese oxide contained in the strontium adsorbent of the present invention can be produced by mixing an aqueous solution of a metal salt containing manganese, an aqueous solution of an alkali metal and an oxidizing agent, and drying the precipitated matter. The production method is characterized in that an aqueous solution of a metal salt containing at least manganese, an aqueous solution of potassium hydroxide and an aqueous solution of sodium peroxodisulfate are mixed at a potassium / manganese molar ratio of 3 to 10, a sodium peroxodisulfate / manganese molar ratio of 0.5 to 4, and a temperature of 0°C to 100°C, the precipitated matter is dried and then pulverized into a powder form.
[0018] The manganese-containing metal salt aqueous solution can be prepared by dissolving a manganese-containing metal salt in water. Examples of manganese-containing metal salts include water-soluble manganese sulfate (II), manganese chloride (II), manganese nitrate (II), manganese acetate (II), and the like, and may be anhydrous or hydrated. Among these, manganese sulfate (II) is most suitable in consideration of waste liquid treatment, corrosiveness, and raw material costs.
[0019] The potassium hydroxide aqueous solution can be of any concentration, but from the viewpoint of productivity, 1 mol / L or more is preferable. The potassium / manganese molar ratio is 3 to 10. If it is less than 3, trimanganese tetroxide (Mn3O4) is by-produced, and if it exceeds 10, trimanganese tetroxide (Mn3O4) is also by-produced. From the viewpoint of strontium adsorption performance, it is preferable that it is 4 to 8.
[0020] The aqueous sodium peroxodisulfate solution can be used at any concentration, but from the viewpoint of productivity, it is preferably 5% or more. The sodium peroxodisulfate / manganese molar ratio is 0.5 to 4. If it is less than 0.5, layered manganese oxide is not produced, and if it exceeds 4, manganese is excessively oxidized to hexavalent manganese ions, which are released into the solution. From the viewpoint of productivity, it is preferably 0.7 to 2, and more preferably 0.7 to 1.2.
[0021] When the metal salt aqueous solution, the potassium hydroxide aqueous solution, and the sodium peroxodisulfate aqueous solution are mixed, either a batch type or a continuous type reaction may be used. As for the method of adding the aqueous solutions, it is preferable to drop them at a constant rate at the same time while keeping the alkali metal / manganese molar ratio and the sodium peroxodisulfate / manganese molar ratio constant, since this leads to a uniform reaction.
[0022] After the reaction, the precipitated substance can be separated by filtration or centrifugation. Any method capable of solid-liquid separation may be used. In this case, it is preferable to wash the precipitated substance to remove by-products such as potassium sulfate and other potassium salts, and unreacted potassium hydroxide.
[0023] There are no particular limitations on the method for drying the precipitate after solid-liquid separation, but drying at a temperature of 600°C or higher is not possible because at such a temperature the manganese oxide changes from a layered structure to a hollandite-type tunnel structure.
[0024] The dried precipitate can be pulverized by any method, such as using a mortar, a ball mill, or a jaw crusher.
[0025] The powder after pulverization can be used as it is as a strontium adsorbent. EXAMPLES
[0026] The present invention will now be described in more detail with reference to examples, but is not limited to these.
[0027] <Measurement of sodium, potassium, and manganese in samples> The composition of the obtained sample was analyzed by inductively coupled plasma optical emission spectrometry (ICP method). That is, 50 mg of sample powder was dissolved in 1 ml of hydrogen peroxide solution and 5 ml of hydrochloric acid, and the solution was diluted to 1 L with ion-exchanged water to prepare a measurement solution. The obtained measurement solution was measured using a general inductively coupled plasma optical emission spectrometry device (product name: OPTIMA3000DV, manufactured by PERKIN ELMER), and the chemical composition of the obtained sample was analyzed. At this time, the molar concentration of potassium in the obtained measurement solution was measured using C Na [mol / L], potassium molar concentration C K [mol / L], the molar concentration of manganese is C Mn The molar ratio x of sodium to manganese and the molar ratio y of potassium to manganese in the sample were calculated.
[0028] x=C Na / C Mn y=C K / C Mn <Powder X-ray diffraction measurement> Using an X-ray diffractometer (trade name: Ultima4, manufactured by Rigaku), powder X-ray diffraction measurement of the obtained sample was performed. For the X-ray source, CuKα rays (λ = 1.5405 Å) were used. The measurement mode was step scan, the scan condition was 0.04° per second, the measurement time was 0.25 seconds, and the measurement range was 5° to 70° in terms of 2θ.
[0029] <Measurement of BET specific surface area> Using a BET specific surface area measuring device (trade name: FlowSorbIII, manufactured by Micromeritics), the BET specific surface area of the obtained sample was measured. For the BET specific surface area measurement, as a pretreatment, a pretreatment device attached to the BET specific surface area measuring device was used, and the sample was heated at 120 °C for 1 hour in a nitrogen stream to remove moisture.
[0030] <Measurement of average particle diameter D 50 > Using a particle size distribution measuring device (trade name: MT3300 EXII, manufactured by Microtrac·BEL), the average particle diameter D 50 (The particle diameter of the sample at 50% of the integrated value based on volume in the particle size distribution obtained using spherical approximation by laser diffraction / scattering method) was measured. At this time, the sample was dispersed in pure water using a standard material circulator for measurement. The calculation of the particle diameter was performed using the function attached to the measurement software attached to the device. At that time, the calculation mode was HRA, the measurement time was 30 seconds, and the refractive index of the particles was set to 2.5.
[0031] <Measurement of strontium adsorption amount> Strontium chloride was dissolved in ion-exchanged water so that the concentration of strontium became 10 mg / L to prepare an aqueous strontium solution.
[0032] 0.05 g of the adsorbent sample was added to 750 mL of the aqueous strontium solution. An adsorption test was conducted by stirring this at 25 °C for 1 hour and obtaining a filtrate (hereinafter, the post-treatment solution) from which the adsorbent sample was removed by suction filtration.
[0033] The strontium concentration in the sample solution was measured by inductively coupled plasma emission spectrometry (ICP method). A general inductively coupled plasma emission spectrometry device (product name: OPTIMA3000DV, manufactured by PERKIN ELMER) was used for the measurement, and the strontium concentration was obtained by measuring the obtained measurement solution.
[0034] The strontium concentration of the strontium aqueous solution before the adsorption test was defined as C0 (mg / L), and the strontium concentration of the solution after treatment was defined as C (mg / L). The strontium removal rate was calculated using the following formula.
[0035] Strontium removal rate (%) = (C0-C) / C0 x 100 Example 1 130g of pure water was placed in a reaction vessel with an internal volume of 1L, and the temperature was raised to 40°C and maintained. Separately, manganese sulfate hexahydrate (special grade reagent, manufactured by Kishida Chemical) was dissolved in pure water to prepare a 2.0mol / L manganese sulfate aqueous solution. In addition, a 40% potassium hydroxide aqueous solution (special grade reagent, manufactured by Kanto Chemical) was diluted with pure water in a separate vessel to prepare a 5mol / L potassium hydroxide aqueous solution. Furthermore, sodium peroxodisulfate (first grade reagent, manufactured by Kishida Chemical) was dissolved in pure water in a separate vessel to prepare a 21% sodium peroxodisulfate aqueous solution. A four-blade paddle blade with an outer diameter of 80mm was inserted into the reaction vessel, and the manganese sulfate aqueous solution, potassium hydroxide aqueous solution, and sodium peroxodisulfate aqueous solution were added to the reaction vessel at the same speed over a period of 20 minutes while stirring by rotating the paddle blade at 600ppm. The addition rate of the manganese sulfate aqueous solution was 5.0 g / min, the addition rate of the potassium hydroxide aqueous solution was 7.7 g / min, and the addition rate of the sodium peroxodisulfate aqueous solution was 9.0 g / min. The potassium / manganese molar ratio was 4, and the sodium peroxodisulfate / manganese molar ratio was 1. After the addition of the aqueous solutions was completed, stirring was continued for another 10 minutes while keeping the container temperature constant. The above operation resulted in a slurry in which potassium-type layered manganese oxide was precipitated. The obtained slurry was filtered and washed with pure water, and the washed wet cake was dried at 60°C for 16 hours to obtain an aggregate of potassium-type layered manganese oxide. The aggregate was ground with an alumina mortar and pestle to obtain a powder of potassium-type layered manganese oxide (strontium adsorbent). The average particle diameter of the powder D 50 was 108 μm.
[0036] The composition of the obtained sample was Na 0.13 K 0.23 The interlayer distance was 7.45 Å, the crystallite diameter was 30 Å, and the BET specific surface area was 4.65 m 2 / g.
[0037] The strontium removal rate of the obtained sample was 70.3%.
[0038] Example 2 The synthesis was carried out in the same manner as in Example 1, except that the addition rate of the potassium hydroxide aqueous solution during synthesis was changed to 12 g / min. The potassium / manganese molar ratio during this synthesis was 6. A potassium-type layered manganese oxide powder (strontium adsorbent) was obtained by this synthesis. The average particle diameter D of the powder 50 was 56.4 μm.
[0039] The composition of the obtained sample was Na 0.11 K 0.25 The interlayer distance was 7.31 Å, the crystallite diameter was 53 Å, and the BET specific surface area was 4.17 m 2 / g.
[0040] The strontium removal rate of the obtained sample was 77.9%.
[0041] Example 3 800g of pure water was placed in a reaction vessel with an internal volume of 1L having an outlet at the top of the vessel, and the temperature was raised to 60°C and maintained. Separately, manganese sulfate was dissolved in pure water to prepare a 0.90mol / L manganese sulfate aqueous solution. In addition, a 40% potassium hydroxide aqueous solution was diluted with pure water in a separate vessel to prepare a 2.3mol / L potassium hydroxide aqueous solution. Furthermore, sodium peroxodisulfate was dissolved in pure water in a separate vessel to prepare a 10% sodium peroxodisulfate aqueous solution. A four-blade paddle blade with an outer diameter of 80mm was inserted into the reaction vessel, and the manganese sulfate aqueous solution, potassium hydroxide aqueous solution, and sodium peroxodisulfate aqueous solution were added to the reaction vessel at the same speed at the same time while stirring by rotating it at 600ppm. The addition rate of the manganese sulfate aqueous solution was 10g / min, the addition rate of the potassium hydroxide aqueous solution was 19g / min, and the addition rate of the sodium peroxodisulfate aqueous solution was 18g / min. The potassium / manganese molar ratio at this time was 5, and the sodium peroxodisulfate / manganese molar ratio was 1. The above operation was carried out continuously for 4 hours. The slurry from which the layered manganese oxide had precipitated continuously flowed out from the outlet at the top of the vessel. The slurry that flowed out between 120 and 160 minutes after the start of synthesis was collected, filtered, and washed with pure water. The washed wet cake was dried at 60°C for 16 hours to obtain an aggregate of potassium-type layered manganese oxide. The aggregate was ground with an alumina mortar and pestle to obtain a powder of potassium-type layered manganese oxide (strontium adsorbent). The average particle diameter of the powder D 50 was 73.5 μm.
[0042] The composition of the obtained sample was Na 0.10 K 0.21 The interlayer distance was 7.26 Å, the crystallite diameter was 31 Å, and the BET specific surface area was 1.44 m 2 / g.
[0043] The strontium removal rate of the obtained sample was 80.8%.
[0044] Comparative Example 1 200g of pure water was placed in a reaction vessel with an internal volume of 1L, and the temperature was raised to 40°C and maintained. Separately, manganese sulfate hexahydrate (special grade reagent, Kishida Chemical) was dissolved in pure water to prepare a 2.0mol / L manganese sulfate aqueous solution. In addition, a 40% potassium hydroxide aqueous solution (special grade reagent, Kanto Chemical) was diluted with pure water in a separate vessel to prepare a 5mol / L potassium hydroxide aqueous solution. Furthermore, a 35% hydrogen peroxide aqueous solution (first grade reagent, Kishida Chemical) was prepared in a separate vessel. A four-blade paddle blade with an outer diameter of 80mm was inserted into the reaction vessel, and the manganese sulfate aqueous solution, potassium hydroxide aqueous solution, and hydrogen peroxide aqueous solution were added to the reaction vessel at a constant speed over 30 minutes while stirring by rotating it at 600ppm. The addition rate of the manganese sulfate aqueous solution was 5.0g / min, the addition rate of the potassium hydroxide aqueous solution was 5.8g / min, and the addition rate of the hydrogen peroxide aqueous solution was 1.6g / min. The potassium / manganese molar ratio at this time was 3, and the hydrogen peroxide / manganese molar ratio was 2. After the addition of the aqueous solution was completed, stirring was continued for a further 10 minutes while maintaining the container temperature constant. The above procedure yielded a slurry in which potassium-type layered manganese oxide had precipitated. The resulting slurry was filtered and washed with pure water, and the washed wet cake was then dried at 60°C for 16 hours to obtain an agglomerate of potassium-type layered manganese oxide. The agglomerate was ground with an alumina mortar and pestle to obtain a powder of potassium-type layered manganese oxide (strontium adsorbent). The powder's average particle size D 50 was 77.0 μm.
[0045] The composition of the obtained sample is K 0.30 The interlayer distance was 7.24 Å, the crystallite diameter was 40 Å, and the BET specific surface area was 0.17 m 2 / g.
[0046] The strontium removal rate of the obtained sample was 63.8%.
[0047] Comparative Example 2 The same procedure as in Comparative Example 1 was carried out except that the synthesis temperature was changed to 60°C, and a potassium-type layered manganese oxide (strontium adsorbent) was obtained. 50 was 139 μm.
[0048] The composition of the obtained sample is K 0.30 The interlayer distance was 7.14 Å, the crystallite diameter was 78 Å, and the BET specific surface area was 0.49 m 2 / g.
[0049] The strontium removal rate of the obtained sample was 44.9%.
[0050] Comparative Example 3 The same procedure as in Comparative Example 1 was carried out except that the synthesis temperature was changed to 80° C. and the addition rate of the potassium hydroxide aqueous solution was changed to 12 g / min, to obtain a potassium-type layered manganese oxide (strontium adsorbent). 50 was 95.5 μm.
[0051] The composition of the obtained sample is K 0.22 The interlayer distance was 7.15 Å, the crystallite diameter was 76 Å, and the BET specific surface area was 44.1 m 2 / g.
[0052] The strontium removal rate of the obtained sample was 61.2%. [Industrial Applicability]
[0053] The strontium adsorbent of the present invention, which contains layered manganese oxide, can be used as an adsorbent for strontium.
Claims
1. The layered manganese oxide contains at least sodium, potassium and manganese, and has the formula Na x K y MnO 2 (wherein 0.05≦x, 0.05≦y, and 0.31≦x+y≦0.60 are satisfied), the crystallite diameter is 20 Å or more and 250 Å or less, and the BET specific surface area is 1 m 2 / g or more 10m 2 / g or less, and the layered manganese oxide has an interlayer distance of 7.0 Å to 7.6 Å, and has an average particle diameter D 50 A strontium adsorbent characterized in that it is a powder having a particle size of 50 μm or more and less than 200 μm.
2. 2. The strontium adsorbent according to claim 1, characterized in that, in the composition formula, the following conditions are satisfied: 0.1≦x, 0.1≦y, and 0.31≦x+y≦0.
60.
3. BET specific surface area is 1m 2 / g or more 5m 2 3. The strontium adsorbent according to claim 1, wherein the strontium adsorbent has a molecular weight of 1 / g or less.
4. 4. The strontium adsorbent according to claim 1, wherein the crystallite size is 30 Å or more and 100 Å or less.
5. 5. The strontium adsorbent according to claim 1, wherein the interlayer distance is 7.1 Å or more and 7.5 Å or less.
6. Average particle diameter D 50 The strontium adsorbent according to any one of claims 1 to 5, characterized in that the particle size is 50 µm or more and 100 µm or less.
7. 7. The method for producing a strontium adsorbent according to any one of claims 1 to 6, characterized in that an aqueous solution of a metal salt containing at least manganese, an aqueous solution of potassium hydroxide and an aqueous solution of sodium peroxodisulfate are mixed at a potassium / manganese molar ratio of 3 to 10 and a sodium peroxodisulfate / manganese molar ratio of 0.5 to 4 at a temperature of 0°C to 100°C, the precipitate is dried and then pulverized into a powder form.
8. 8. The method for producing a strontium adsorbent according to claim 7, wherein the aqueous metal salt solution is an aqueous manganese sulfate or manganese nitrate solution.
Citation Information
Patent Citations
JP15042A
Manganic acid nanosheet and production method therefor
JP2003335522A
Layered manganese oxide porous body having aluminum hydroxide cross-link structure and method for producing the same
JP2005139051A
Ammonium ion adsorbent and ammonium ion removing method
JP2006021132A
Strontium ion adsorbent and method for producing the same
JP2020015042A
